Problems of the state of internal and external development of the kazakh state in the stage of strength, rise (Journal of actual problems of jurisprudence, 2020)
Turning to historical data, we believe that the XVI-XVII centuries was one of the most difficult and historically responsible periods in the formation of the Kazakh people as a nation, the comprehensive strengthening of our statehood politically, socially and economically. Because during this period, the Kazakh people achieved political unity, unity and solidarity, created and established their own state. Before the establishment of the Kazakh state, the Kazakh tribes, which belonged to four independent khanates – Abulkhair Khanate, Moghul Khanate, Nogai Union, Siberian Khanate, are now united in a single shanyrak of a single Kazakh Khanate. Unified into the ethnic territory and khanate of the Kazakhs, that is, the Kazakh state at that time covered almost the entire territory of modern Kazakhstan. This unification has finally completed the long-standing process of formation of the Kazakh people. The methodological approaches used in the article were used in the form of historical-comparative, dialectical-applied. It is one of the new works studied on the basis of materials obtained in the documentary framework archives of the historical periods of the Kazakh state. Despite the fact that the Kazakh people have achieved ethnic, national, state unity and independence, the country has gone through a difficult period of political instability, both internally and externally. This situation is explained by both objective and subjective reasons. Key words: Abulkhair khan, Moghulstan, Nogai Horde, Tauekel khan, Esim khan, Tursyn khan, А. Levshin, Kultobe, Maslikhat, Salkam Zhangir, Ermak, Kushim khan, Tahir khan, Orazmuhammed, Turkestan, Kasymov khanate, Kadyrgali Zhalayri.